The role of polyamines in anti-proliferative effect of selected malaysian herbs in human lung adenocarcinoma cell line - Abdul Ghani, Radiah; Jamil, Elyna Fatini; Nor Azahan Shah, Nor Azni Masturah; Nik Abdul Malek, Nik Nurasyikin (Universiti Teknologi Malaysia, 2015)
Polyamine is a group of aliphatic amine that is necessary for cell growth and development. However, potential of developing cancer is enhanced with the increase of polyamine levels in the body. Since polyamines can be obtained through diet intake, it is essential for cancer patients to consume foods that have low level of polyamines. Therefore, this study aims to determine the polyamine level of selected plants; Sabah Snake Grass (Clinacanthus nutans), Daun Kadok (Piper sarmentosum) and Fig (Ficus auriculata). The antiproliferative effects of C. nutans, P. sarmentosum and F. auriculata were investigated using MTT assay and the polyamines content in these plants and intracellular content were quantified using High Performance Liquid Chromatography (HPLC). The results showed that polyamines content in C. nutans (41.49 nmol/g), P. sarmentosum (55.01 nmol/g) anf F. auriculata (39.28 nmol/g) were classified under low level. The IC50 values for these plants were in the range of 20-30 mg/ml. This study demonstrated that these plants inhibit the A549 cell’s growth after 24 hours to 96 hours of exposure. Depletion of intracellular polyamine after 48 hours to 96 hours of exposure was also identified. In conclusion, the study showed that C. nutans, P. sarmentosum and F.auriculata contain low level of polyamine and have anti-proliferative effect against A549 cells. Therefore these plants are recommended to reduce or delayed the occurrence of malignancy and prevention of cancer recurrence after successful treatment.